The First Diagnosed Case of Steroid-induced Kaposi's Sarcoma in Mongolia - Byamba, Khandsuren; Munkhbayar, Ariunaa; Batsaikhan, Oyuntsatsral; Sainzaya, Undram (Central Asian Journal of Medical Sciences, 2016)
Objectives: Kaposi's sarcoma (KS) is a vascular neoplasm with four main types. We report the first diagnosed case of steroid-induced KS in a non-HIV patient in Mongolia. Methods: A 57-year-old man presented hemorrhagic spots on his body after seven months of corticosteroid therapy due to the glomerulonephritis. Upon examination, the morphology, histopathology and immunohistochemistry indicated human herpes virus-8 (HHV-8) positive KS. Results: After the dose reduction of corticosteroids the lesions remarkably diminished in size and almost resolved as observed at the six-month follow-up. Conclusion: Medical professionals should be aware of the appearance of KS in patients receiving immunosuppressive therapies.